A Study on the Effects of the Use of Propofol in Experimental Model Inferior Epigastric Island Flap on Ischemia-Reperfusion Injury. Issue 8 (November 2017) - Eroglu, Tuncay; Bozkurt, Mehmet; Kapi, Emin; Selcuk, Caferi Tayyar; Kuvat, Samet Vasfi; Tufek, Adnan; Isik, Fatma Birgul; Bozarslan, Beri Hocaoglu; Firat, Ugur; Satici, Omer
Abstract : Abstract: Problems concerning vascular blood flow are the most frequently encountered ones after flap applications. The flap tissue starts to develop ischemia in patients with a vascular blood flow insufficiency. And reperfusion starts in those patients in whom the ischemia is temporary, triggering an ischemia-reperfusion injury depending on the duration of the ischemia. The aim of this study was to evaluate the effect of propofol, which is an anesthetic agent known to have an antioxidant effect and a free radical scavenging feature on the ischemia-reperfusion injury created on an experimental epigastric island flap. Thirty Sprague–Dawley rats were used in the study. The rats were divided into 3 groups of 10 rats each. Inferior epigastric artery-based abdominal flaps were prepared in all the groups. In group 1 (sham), the flap was elevated but no ischemia was applied. In groups 2 (control) and 3 (propofol), the flap was exposed to ischemia for 2 hours after it was elevated. All the rats were sacrificed and biochemical and histopathological assessments were made on the tissue samples taken on the 14th day. As a result of a comparison between the groups, the flap viability rates and the superoxide dismutase, total antioxidant capacity, and catalase values were found to be significantly higher ( P  < 0.001) in the propofol group while the malondialdehyde and total oxidative stress values were lower ( P  < 0.001). Based on the data obtained from the present study, the use of propofol was observed to have a protective effect against ischemia-reperfusion injuries in flap surgeries.